Neonatal Sucking Blister and Sucking Pads: Coexisting Simultaneously in a 24 Hour Old Newborn - Arega G; Admasse SD; Alemneh D (Dove Medical Press, 2022)
Gashaw Arega, Selamawit Daniel Admasse, Desalegn Alemneh Addis Ababa University, School of Medicine, Department of Pediatrics and Child Health, Addis Ababa, EthiopiaCorrespondence: Gashaw Arega, Addis Ababa University, School of Medicine, Department of Pediatrics and Child Health, P.O. Box: 9080, Addis Ababa, Ethiopia, Tel +251911417235, Email gashawarega@gmail.comAbstract: Neonatal suckling blisters usually present as benign skin erosions involving the distal upper extremities at birth presumably induced by vigorous sucking in utero, whereas sucking pads commonly appear as hyperkeratotic thickening of the lips indicating effective neonatal sucking reflex. These benign neonatal conditions should be differentiated from other serious systemic and dermatological diseases in newborns through their clinical manifestations and self-limited course. Here, we report a 24 hour old male newborn with a sucking blister and sucking pads present at birth coexisting simultaneously, diagnosed based on the presentation and benign course. A high index of clinical suspicion is required to avoid unnecessary investigations and treatment.Keywords: newborn, neonatal sucking blisters, sucking pads